2010
DOI: 10.3162/036298010791170169
|View full text |Cite
|
Sign up to set email alerts
|

The Logic of Legislative Leadership: Preferences, Challenges, and the Speaker's Powers

Abstract: Principal agent theory implies that legislators will delegate power to a leader only when they need the leader's help and the leader can be expected to provide satisfactory help if granted power. This study is the first to evaluate the implied interaction between legislators' need for help and the degree to which legislators and leaders have similar preferences. By analyzing the Speaker's powers in the U.S. states, I arrived at three key conclusions. First, institutional leadership power responds to the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 29 publications
0
42
2
Order By: Relevance
“…Thus, this index covered the range of dimensions of legislative leadership powers commonly discussed in the literature. Scholars have used it or its components successfully as both a dependent (Richman 2010) and an independent (Burden 2005;Hedlund et al 2009;S. M. Miller, Nicholson-Crotty, and Nicholson-Crotty 2011;Overby, Kazee, and Prince 2004) variable, further demonstrating its criterion-related validity.…”
Section: Measuring State Speaker Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this index covered the range of dimensions of legislative leadership powers commonly discussed in the literature. Scholars have used it or its components successfully as both a dependent (Richman 2010) and an independent (Burden 2005;Hedlund et al 2009;S. M. Miller, Nicholson-Crotty, and Nicholson-Crotty 2011;Overby, Kazee, and Prince 2004) variable, further demonstrating its criterion-related validity.…”
Section: Measuring State Speaker Powermentioning
confidence: 99%
“…At the same time, the average score for the 49 state speakers changes very little over this period, suggesting little in the way of a national trend. Thus, these within-state, overtime changes justify both the use of this variable ' Formal Powers Index, 1981-2010: States with Odd-Numbered-Year Legislative Elections. States 1982-83 1984-85 1986-87 1988-89 1990-91 1992-93 1994-95 1996-97 1998-99 2000-01 2002-03 2004-05 2006-07 2008 Note: This index is developed as discussed in the appendix with data drawn from The Book of the States (Council of State Governments, various years).…”
Section: An Overtime Measure Of State Speakers' Formal Powersmentioning
confidence: 99%
“…We then exploit the cross‐state comparative leverage of our dataset to test theories that attempt to explain variation in party strength. We find substantial evidence that party influence is explained by state socioeconomic diversity, by careerism, and conditionally by variables drawn from the conditional party government literature (Aldrich and Battista 2002; Rohde 1991) along the lines suggested by Richman (2010).…”
mentioning
confidence: 73%
“…Martorano (2004) examined a sample of 23 chambers from 1955 to 1995 and found that larger majorities are associated with fewer minority rights, and that party strength responded to the use of joint rules but not to professionalism. Richman (2010) reanalyzed Clucas' (2001) data, showing that the effects of preference polarization on leadership power depend upon the extent to which legislators faced substantial challenges.…”
Section: Why Are Some Parties Stronger Than Others?mentioning
confidence: 99%
See 1 more Smart Citation